(untitled) (Al-Academy, 2017)
Aesthetic performance in the mobile sculpturesAli Abd Almohsen AliAbstractChapters of this research are discussed one of the turning points in the In the history of sculpture, which sparked a debate in artistic circles, namely the introduction of the actual movement in sculpture . The researcher highlighted on one of the corners of the controversy on this subject for discussion and looking in and Found results contribute to answer some questions . the Beginning been allocated to the statement of this Research Methodology , research problem, and its importance, and its goal, and borders , the main problem is Lack of clarity of the concept of real motion (physical) in the sculpture , And how the audience understand the aspects of aesthetic in it . and then Put a question: Where are the aspects of beauty in this statue motion ? . There is an essential need to access paid on this subject as a contemporary links between the technical aspects of aesthetic and scientific. And manifested the importance of research as a simple reference , In view of lack of resources on this subject in the Arabic libraries As well as keep us up with the evolution of the art of sculpture. The search have goal to detect the aspects of beauty in the performance of mobile sculptures. and followed all this systematic side of the search is an access to the subject of motion , within the theoretical framework in the first three sections discussed a new beauty in the movement and the liberation of statue from rigidity since the Renaissance days. The second section has introduced a series of experiments carried out by the artists of the modern era included the application of the actual motion on several works Represent the core for the emergence of kinetic sculpture , A new direction in art and sculpture , which was discussed in the third section. Turning to research procedures, which included identifying research society and sample selection and search tool, to begin after the analysis of that sample and out the results and conclusions of the answer the problem of the research.